The Indonesian Constitutional System in the Post Amendement of the 1945 Constitution - Zen Zen Zanibar (Sriwijaya Law Review, 2018)
The 1945 Constitution of the Republic of Indonesia was amended for four times between 1999 and 2002) in the reformation era. These constitutional changes have altered the principles and the structure of the Indonesian primary state‟s institutions. Broadly speaking, all of the power branches – i.e. legislative, executive and judiciary organs– are now interrelated horizontally in running the country and none of them is superior to the others. Such constitu-tional system is generally found in countries that employ a presidential system. However, by reviewing the authority hold by the legislatures, it is found that some characteristics of a parlia-mentary system are also applied in Indonesia